What can phylodynamics bring to animal health research?. (September 2021) - Guinat, Claire; Vergne, Timothee; Kocher, Arthur; Chakraborty, Debapryio; Paul, Mathilde C.; Ducatez, Mariette; Stadler, Tanja
Abstract : Infectious diseases are a major burden to global economies, and public and animal health. To date, quantifying the spread of infectious diseases to inform policy making has traditionally relied on epidemiological data collected during epidemics. However, interest has grown in recent phylodynamic techniques to infer pathogen transmission dynamics from genetic data. Here, we provide examples of where this new discipline has enhanced disease management in public health and illustrate how it could be further applied in animal health. In particular, we describe how phylodynamics can address fundamental epidemiological questions, such as inferring key transmission parameters in animal populations and quantifying spillover events at the wildlife–livestock interface, and generate important insights for the design of more effective control strategies. Highlights: Phylodynamics, an increasingly popular statistical framework to infer pathogen transmission dynamics from genetic data, remains overlooked in animal health research. This restricts our ability to design more effective disease control strategies. Phylodynamics can be valuable when investigating the determinants of disease spread, allowing the better targeting of animal populations for disease control and reducing the impact of epidemics. The wildlife–livestock–human interface is critical for disease emergence; thus, promoting phylodynamics at this interface should improve our ability to manage complex epidemics. There is a critical need to improve capacity-building efforts for infectious disease detection in hard-to-sample populations, such as wildlife. Collaborative efforts are needed to make genetic data publicly available in a timely manner during animal disease outbreaks.